KAJIAN TEKNIS DAN EKONOMI PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) DI SUNGAI LEMATANG KOTA PAGAR ALAM - Wibowo, Handy; Daud, Arifin; Al Amin, M. Baitullah (CANTILEVER, 2015)
Indonesia has a potential of renewable energy resources for mini-hydropower up to 450 MW. The energy resources development in Indonesia refers to Presidential Decree No.5/2006 on National Energy Policy, where the government aims to increase the capacity installed in micro-hydro power plants become 2,846 MW by year 2025. Pagar Alam City is a hilly area with an altitude range of 400 m â 3,400 m above sea level. The topography varies from 0Â° - 15Â°, to 45Â° slope. The average rainfall ranges 1,462 - 5,199 mm per year. In addition, Pagar Alam has several rivers, one of them is Lematang River. These conditions make Pagar Alam supposed to become potential area to develop micro-hydro power plants. This study deals with the planning of a micro-hydro power plant within Lematang River based on engineering and economic aspects. The study was done through several steps, i.e. 1) surveying and collecting data of river discharges, rainfall intensity, climatology parameters, and topographic map; 2) analysis of water availability, 3) hydraulic head analysis, 4) analysis of generated power for micro-hydro power plant, and 5) investment feasibility analysis for the constructions. The results of this study show that the availability of water in the river is 3.076 m3/s, the net hydraulic head is 11.442 m, the generated power is 165 kW for total efficiencies 47.9%, and the annual hydroelectricity production is 1.3 GWh/year. The investment feasibility analysis for the construction indicates that the planning of micro-hydro power plant development is feasible to implement.Key Words: hydropower, green energy, micro-hydro, engineering economics